AMBANG DETEKSI DAN PREFERENSI RASA UMAMI DALAM MODEL PANGAN - Dede Robiatul Adawiyah; Febby Setiawan (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2017)
Umami is one of the basic taste produced by monosodium glutamate (MSG). Generally, commercial MSG products did not specify the amount of a certain dose to produce palatable food. This problem could lead to uncontrolled and excessive use of MSG by consumers. The aim of this study was to determine the values for the detection and preference threshold of umami taste from commercial MSG products at different salt level. The detection threshold was determined using R-index method in salt solutions. The preference threshold was determined by using hedonic rating in food model. A food model selected in this case is spinach soup that is commonly consumed by Indonesian. The salt concentrations for detection and preference threshold experiment were 0.42 and 0.30 g/100 mL. Umami taste preference threshold value using Fechner’s psychophysic equation for 0.30 g/100 mL salt concentration is 0.25 g MSG/100 mL, while for 0.42 g/100 mL salt concentration, the umami taste preference threshold value is 0.06 g MSG/100 mL. Detection threshold value using R-index method for 0.30 g/100 mL salt concentration is 0.05 g MSG/100 mL, while for 0.42 g/100 mL salt concentration is 0.02 g MSG/100 mL. Different salt concentrations leads to differences in the values of threshold preferences and detection threshold of the umami taste of MSG. Increasing salt concentration tends to decrease the detection and preference threshold of umami taste from MSG. This research results could be used as the basic information in food product formulation such as seasoning and condiment using mixtures of salt and MSG.